Colorimetric detection of hydrogen peroxide using silver nanoparticles with three different morphologies. Issue 37 (2nd September 2016) - Zhang, Laiping; Li, Li
Abstract : We attempted to investigate the colorimetric detection of H2 O2 using silver nanoparticles (AgNPs) with three different morphologies (triangular, spherical, and cubic), and the activity of AgNPs toward H2 O2 increased in the order of cubic < spherical < triangular AgNPs. Abstract : We attempted to investigate the colorimetric detection of H2 O2 using silver nanoparticles (AgNPs) with three different morphologies (triangular, spherical, and cubic), and the activity of AgNPs toward H2 O2 increased in the order of cubic < spherical < triangular AgNPs.